The use of cutting/positioning devices for custom-fitted temporomandibular joint alloplastic reconstruction: current knowledge and development of a new system. Issue 4 (April 2021) - Sembronio, S.; Tel, A.; Robiony, M.
Abstract: Alloplastic replacement of the temporomandibular joint (TMJ) is the treatment of choice in cases of TMJ end-stage disease. Improvements in computer-aided design/computer-aided manufacturing (CAD/CAM) translated into the possibility ongf designi very precise TMJ prostheses based on the anatomy of each single patient. Custom-made TMJ prostheses are described in the most recent literature and provide facilitations in terms of ease of placement and accuracy. Although before the era of custom-made surgical guides, they did not play a prominent role in the field of TMJ surgery, their use has become mandatory when custom-made prostheses are used. Surgical guides, generally known also as cutting guides, allow the subcondylar bone cut to be performed according to the exact shape and size of the planned prostheses. Additionally, they allow the predrilling of fixation holes in the mandible to minimize errors in prostheses positioning. However, the design of surgical guides did not evolve over time as much as prostheses did. In this paper the authors critically analysed literature on this topic and described the improvements of surgical guides over time. Moreover, based on the findings of literature research, a new cutting guide system was developed and is proposed in this article.